2011
DOI: 10.2514/1.48239
|View full text |Cite
|
Sign up to set email alerts
|

Entry, Descent, and Landing Performance of the Mars Phoenix Lander

Abstract: On May 25, 2008, the Mars Phoenix Lander successfully landed on the northern arctic plains of Mars. An overview of a preliminary reconstruction analysis performed on each entry, descent, and landing phase to assess the performance of Phoenix as it descended is presented and a comparison to pre-entry predictions is provided. The landing occurred 21 km further downrange than the predicted landing location. Analysis of the flight data revealed that the primary cause of Phoenix's downrange landing was a higher tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…The test cases started with a simple vertical drop from rest of the fully deployed parachute and capsule, and then gradually increased the simulation complexity to include parachute opening, lander deployment, retrorocket firing, and other effects. The POST II model had been previously compared and validated to a MATLAB-based simulation and another multi-degree-of-freedom simulation [7,8]. In each case, the agreement between the simulations was excellent.…”
Section: Model Verificationmentioning
confidence: 96%
See 2 more Smart Citations
“…The test cases started with a simple vertical drop from rest of the fully deployed parachute and capsule, and then gradually increased the simulation complexity to include parachute opening, lander deployment, retrorocket firing, and other effects. The POST II model had been previously compared and validated to a MATLAB-based simulation and another multi-degree-of-freedom simulation [7,8]. In each case, the agreement between the simulations was excellent.…”
Section: Model Verificationmentioning
confidence: 96%
“…These results showed that the multibody parachute system reliably damped out rotational motion of the capsule. This rotational damping was of great interest [8,9].…”
Section: Monte Carlo Simulationmentioning
confidence: 98%
See 1 more Smart Citation
“…The flight trajectory went from northwest to southeast and the actual landing site has been identified to lie just to the left of center of the circular area (marked by a cross hair). The actual landing site was 21 km downtrack and 5.3 km crosstrack from the final preentry prediction for reasons discussed in [2]. The crater to the right of the landing site is Heimdal Crater.…”
Section: Introductionmentioning
confidence: 99%
“…1. The ellipse outlines the area where Phoenix was predicted to land before arriving at Mars and has a size of 55.1 by 19.2 km [2]. The flight trajectory went from northwest to southeast and the actual landing site has been identified to lie just to the left of center of the circular area (marked by a cross hair).…”
Section: Introductionmentioning
confidence: 99%